A Nietzschean transhumanism? On the partiality of the plea - García-Granero, Marina (Logos. Anales del Seminario de Metafísica, 2020)
The article analyzes from a critical perspective the attempts to interpret Nietzsche as a precursor to transhumanism. After a brief contextualization of the fruitful debate concerning Nietzsche and transhumanism, the paper evaluates the partial or fractional character of Stefan Sorgner’s plea for a “Nietzschean transhumanism”. Then, it considers the tension between humanity, the overcoming of the human being and their breeding in Nietzsche’s writings. Once this analysis is carried out, and without the intention of falling into anachronism, it is argued that Nietzsche certainly anticipates a seed of “post-humanity”, with his critique of humanistic culture and his invitation to both transform the human being and to overcome nihilism, but this idea of post-humanity should not be assimilated to the technological ideal of transhumanism. As a way of conclusion, a prospective analysis of transhumanism from a Nietzschean perspective is suggested, using as a way of example the image of the “shadows of God”.